Enhancing Numeracy and Literacy Skills of Grade I Pupils through a Parent-Induced Learning Program: Ilaw sa Lilim for Para Teachers Coping with Bereavement (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
Literacy refers to the ability of learners to comprehend, analyze, and creatively construct written and printed materials associated with various contexts, whereas numeracy refers to the ability to analyze and interpret numerical principles (UNESCO). The active involvement and participation of the parents in the education of their child is far greater now in the new normal compared to the previous setting. This study aimed to determine the effectiveness of parent-induced learning, namely "Ilaw Sa Lilim Ang Para teachers Kong Natay": an intervention program to enhance Grade I Pupils’ Numeracy and Literacy Skills. Through descriptive research design, the study involved 11 parents of those pupils who struggle with language literacy and numeracy who had voluntarily undergone online parental training for two weeks. Also, the statistical tools used in this study were mean, standard deviation, and dependent t-test.  Through the mean scores in pre-test and post-test, the results showed that pupils scored in language literacy in terms of phonological awareness, alphabet knowledge, fluency, and reading comprehension. And in numeracy skills in terms of counting, basic arithmetic, number symbols, and recognizing symbols, all significantly improved their rating after the intervention program. The results also revealed a significant difference between the pre-test and post-test mean scores of Grade 1 Pupils in Language Literacy and Numeracy Skills indicating an improvement in their statistical value. Thus, the researcher recommends strengthening the communication link among the parents by tapping them to be actively involved in school and academic-related activities. Also, integrate the intervention program into the curriculum to consistently check and upgrade its needs and applicability, especially in the challenge of the new normal, by considering including it in any future training among the parents. Effective, practical, and feasible pedagogical skills that would meet the different learning styles and interests of the children so as to maintain their span of attention.